Seleksi Progeni F1 Hasil Persilangan Tetua Betina IRR 111 dengan Beberapa Tetua Jantan 2006Pada Tanaman Karet(Hevea brassiliensis Muell Arg.). - Sulvizar Musranda; Rosmayati Rosmayati; Revandy Iskandar M. Damanik. (Universitas Sumatera Utara, 2015)
The objective of this research is to get the best progeny based on potential of latex yieldcharacteristic, timber yield characteristic and latex-timber yield resulted from 2006 hand pollinationThe research wasconducted in ± 54 m above sea level at Balai Penelitian Sungei Putih PusatPenelitian Karet Galang Deli Serdang Sumatera Utara Medan from February2014 - July 2014. Theresearch is done by measuring coefisien varians, correlation, regression, path analysis, 10 % and 1% selection intensity, and two line pattern.The research showed based on selection latex yield are 115/06 and 136/06 (intensity 10% and 1%),based on selection timber yield with intensity 10 % are 100/06, 4/06, 25/06, 41/06, 150/06, 29/06and intensity 1 % is 100/06, progeny 136/06 and 29/06 are potential progenies as latex and timberyield for cross 2006 with girth and diameter of latex vessels had directeffect for latex yield andcomponent girth and height of primary branches had direct effect for timberyield. Key words : Hevea brasiliensis, progeny, path analysis, selection